Dampak Resolusi Konflik Melalui Interaksi Sosial Warga Beragama di Lingkup Warga Perumahan Cibipark Residence Kecamatan Cibinong Kabupaten Bogor - Nur Qomariyah; Trie Yunita Sari (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, 2024)
This research discusses the social interaction between Muslim and non- Muslim residents in Cibipark Residence Housing, Cibinong District, Bogor Regency, which consists of three different religious groups: Islam, Christianity, and Hinduism. It is a qualitative study obtaining data through observation, interviews, and documentation using a smartphone for recording and photos, employing a sociological approach. The results reveal various forms of interaction where Muslim and non-Muslim residents blend together to resolve conflicts, particularly regarding land and public facilities, marked by cooperation and accommodation. Residents are capable of managing conflicts without resorting to violence, relying on consensus-building, and no economic competition or religion- based sentiments were found. Supportive factors for social interaction include sympathy and the integrity of residents, most of whom are law enforcement officers, in promoting tolerance. However, the scarcity of places of worship for non-Muslim residents poses a potential conflict challenge in the future.